Neonatal survival in the Republic of Moldova – cost-effective evidence-based interventions. (20th October 2014) - Stratulat, Petru; Curteanu, Ala; Caraus, Tatiana
Abstract: Aim : To estimate the number of preventable neonatal deaths based on national data. Methods : To estimate the number and proportions of avoidable neonatal deaths, we have used the same approach described by Gary L. Darmstadt, using both the official statistical data and data of some assessment studies carried out in the country. Results : According to the calculations, the highest number of neonatal deaths we are able to prevent can be obtained from the implementation of evidence-based interventions in the frame of facility-based immediate neonatal and skilled maternal care (14 death prevented at 90% of intervention coverage and 46 deaths at 99% of intervention coverage), the early neonatal mortality rate can be reduced by 7.3% and by 24%, respectively. The second place belongs to facility-based emergency obstetric and antenatal care with an equal number of deaths that could be prevented (14 cases at 90% of intervention coverage and 35 cases at 99% of coverage). Conclusions : We can conclude that due to common efforts of primary, facility-based care and public health sectors, 90% of coverage of perinatal cost-effective qualitatively implemented interventions could prevent 83 neonatal deaths (43%), while 99% of coverage could prevent 142 deaths (74%).